Use of Thermal Images by Nursing professionals - EDUARDO BORBA NEVES (Universidad Nacional de Córdoba, 2020)
The aim of this text was to describe the possibilities of thermal image usage in nursing practice. Thermal images are obtained using infrared cameras that capture the radiation emitted by the skin. Thermal images can be used to: prevention of developing a pressure ulcer (PU) in hospitalized individuals, the clinical monitoring of postoperative patients for Deep Vein Thrombosis, monitoring the skin temperature of the surgical scar can help to prospectively determine whether an area of the skin will evolve into necrosis, and to search for signs and symptoms of phlebitis and infiltration. In this sense, the acquisition of this kind of equipment for use in nursing services is quite feasible, whether in intensive care units, intermediate care units or even in postoperative inpatient units.